Biogeochemical time lags may delay responses of streams to ecological restoration - HAMILTON, STEPHEN K. (Freshwater biology, 2012)
Summary 1. Mounting interest in ecological restoration of streams and rivers, including that motivated by the Water Framework Directive, has stimulated examination of whether management and restoration measures in streams and their catchments have yielded measurable improvements in ecological status (‘health’). Evidence for the efficacy of diffuse‐source pollution reduction (including best management practices on land) has proven elusive. 2. Several hydrological and biogeochemical processes delay the responses of streams and rivers to a decrease in nutrient and sediment inputs, potentially for decades. The implications of such time lags in response to restoration may not be well appreciated by restoration ecologists, regulators, sponsors of restoration work or the broader community. 3. The groundwater time lag results from the long residence time of ground water. This is particularly important with respect to nitrate, but is increasingly important for phosphorus (P) as well. Isotopic tracers and groundwater age dating suggest that stream water often is more than a decade old, and that several decades are required to flush most soluble contaminants from groundwater reservoirs. 4. Sediment movement through river networks can be protracted because of storage and remobilisation processes involving stream beds, impounded reaches and fringing bars and floodplains. In lowland streams and rivers, sediment accretion can be rapid, but its removal is often far slower and can take decades to centuries. 5. Phosphorus availability is subject to time lags because P tends to associate with minerals, resulting in a potentially large yet exchangeable P reserve in upland soils and alluvial and stream‐bed sediments. Thus, soils and sediments can remain rich in P for decades after new inputs are reduced, potentially acting as a source of P to surface waters. Phosphorus saturation of soils along groundwater percolation pathways can lead to even longer time lags. Restoration measures that inundate previously dry soils or desiccate previously inundated sediments can induce high rates of P release. 6. These hydrological and biogeochemical time lags can obscure the short‐term responses of streams and rivers to restoration measures. In many eutrophic waters, large decreases in nutrient availability would be required to return the ecosystem to a natural nutrient‐limited state, and this could take decades.